Nanoencapsulation by ionic gelation of polyphenols from srtichoke (Cynara scolymus L.) residues using ultrasound - Huamán de la Cruz, Alex Rubén (2023)
Background. Artichoke (Cynara scolymus L.) residues are a rich source of phenolic compounds, but these compounds are susceptible to external factors. Therefore, nanoencapsulation by ionic and ultrasound-assisted gelation techniques can be used as an alternative to preservation. This work aimed to determine the effects of the interaction of the following variables: chitosan (Ch) concentration, sodium tripolyphosphate (TPP), Ch/TPP ratio, pH, and sonication time to ensure high encapsulation efficiency (%EE). Materials and methods. Optimal nanoencapsulation conditions were evaluated using a 25–1 fractional factorial design to maximize nanoencapsulation efficiency (%EE) using multivariate regression analysis. Results. The model was adequate with R2 = 0.998. The optimum conditions for nanoencapsulation were Ch (0.28%), TPP (0.29%), Ch/TPP (5/1), pH (4.9) and sonication time (4.79 min). Under these conditions, a %EE of 69.9 ±0.67%, a particle size between 72.3 nm and 460.7 nm, a polydispersity of 0.458, and a charged Z potential of +15.73 mV were determined. In addition, the results showed a good loading of DPPH radical cutting activity 24.21 mM TE and Trolox equivalent antioxidant capacity (TEAC) of 16.45 mM TE in the nanocapsules, which allowed the antioxidant activity of polyphenols to be maintained. Conclusions. The 25–1 fractional factorial design was successfully applied to optimize the individual and interactive effects of the variables during the gelation nanoencapsulation process of artichoke waste polyphenols. Experimental and predicted values showed closely related values. Finally, the nanocapsules obtained with the highest %EE were characterized by particle size, Z-potential and polydispersity index (PDI) and showed good DPPH radical scavenging antioxidant activity loading and Trolox equivalent antioxidant capacity (TEAC).